Development Problems of the Regional Agro-Industrial Complex Management System - Kitovich Tkhakushinov, Edward; Aslanovna Hachemizova, Emma (International Journal of Engineering and Technology, 2018)
The present article deals with the problems concerning ensuring the effective management of the agro-industrial complex in the region, which determines the status and development of the country's economy. The process of improving the agro-industrial complex structure is being considered, which, based on the variety of forms of management and features of land properties and other means of production, should result in the formation of mixed agrarian economy and initiate attempts to create an agricultural market with the competitive environment. The authors substantiate the necessity of state monitoring and analysis of the effectiveness of decisions taken based on new approaches to the agro-industrial complex management in the region, taking into account the numerous forms of agricultural enterprises’ specialization, the competition of individual sectors, the characteristics of regional markets, foreign economic factors, as well as preferences and traditions of social medium. At that, the paramount importance is given to methods and means of forming and organizing anti-crisis management systems, which would take into account the possibility of anticipating crisis situations, assessing the likely losses of the state on the basis of monitoring of the internal and external environment of the management object.